Pelatihan pembuatan media pembelajaran yang kreatif, efektif dan menarik pada guru sekolah dasar di SD Negeri 35 Pare-Pare - Ila Israwaty; Yulia Yulia (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The importance of using media to support the learning process. Making learning media that is creative, effective and interesting is expected to be applied by teachers in primary schools. In the present time, the learning process is not enough if it is not accompanied by learning media. Making learning media does not have to be expensive because it is made using economical materials. Parepare 35 Public Elementary School is one of the Elementary Schools which is a partner of the UNare Parepare V campus. With the condition of the lack of knowledge of teachers at the school about the creation and use of learning media that are creative, effective and interesting. With the training in making learning media that is creative, effective and fun, it can provide knowledge and experience in making creative, effective and interesting learning media, so that the learning process can run smoothly and learning objectives can be achieved.